Synthesis and antitumour evaluation of 4-bromophenyl semicarbazones - Pandeya S.N.; Yogeeswari P.; Sausville E.A.; Mauger A.B.; Narayanan V.L. (My University, 2025)
4-Bromophenyl semicarbazone derivatives have been synthesized and their chemical structures have been confirmed by means of their IR, 1H-NMR data and by elemental analyses. The in vitro evaluation in the 3-cell line, one dose primary anticancer assay is described. The 4-bromo substituted p-nitrobenzylidene phenyl semicarbazone (5) showed significant activity against breast MCF7 cell line and was further evaluated for potential anticancer activity in an in vitro human disease-oriented tumour cell line screening panel that consisted of 59 human tumour cell lines arranged in nine subpanels, representing diverse histologies. Melanoma UACC-62 cell line was relatively more sensitive to compounds 5 (growth inhibition: GI50 = 15.3 μmol/l).